Actions for Recovery and Impleaders in Colombian Case Law, 2001-2009 - Calderón, Paola Andrea (DIXI, 2016)
Topic and Scope: Ths article is the result of the investigation “Effctiveness of Action for Recovery on the Territorial Entities of the Amazon Region of Colombia from 2001 to 2008.” Ths investigation was carried out for the completion of a Master of Administrative Law degree from the Universidad Libre, aiming to establish how Colombian case law has treated the legal concept of actions for recovery and impleaders for the purposes of recovery. Methodology: Th method consisted of a review of literature and pronouncements related to these mechanisms made by the main courts of the country until 2009. Findings: Th results of the analysis allowed the specifiation of their legal nature, concepts connected to their operation, characteristics, and purposes, among other aspects that will lead to better understanding of the legal concept. Conclusions: It was thus concluded that actions for recovery and impleaders for the purposes of recovery are an important mechanism to ensure that public entities recover those disbursements resulting from sentences and other mechanisms of conflct resolution, as case law has facilitated this task through legal tools adopted by the legislature for that purpose.